Highly Ordered Nanoring Arrays Formed by Templated Si‐Containing Triblock Terpolymer Thin Films. Issue 12 (16th January 2017) - Aissou, Karim; Mumtaz, Muhammad; Marcasuzaa, Pierre; Brochon, Cyril; Cloutet, Eric; Fleury, Guillaume; Hadziioannou, Georges
Abstract : Laterally ordered nanorings with a periodicity of 38 nm are produced from the directed self‐assembly of poly(1, 1‐dimethylsilacyclobutane)‐ block ‐polystyrene‐ block ‐poly(methyl methacrylate) thin films on topographically patterned substrates. Such nanoscale arrays with vertically oriented rings are highly desired in technological applications including memory using magnetic recording, metamaterial, waveguide, etc.